Health Informatics: An Introduction - Setiawan, I Made Agus (Jurnal Ilmu Komputer; Vol 6 No 1: April 2013, 2013)
Health informatics is a growing field that employs computer and information science into health sectortowards providing higher quality patient care through better management and availability ofinformation. However, the terminology of health informatics is poorly understood and not even agreedupon by academics and professionals. This paper will discuss and elaborate the field of healthinformatics including various terminologies and definition as well as the benefit for health sector andits challenges.
Keywords: Health Informatics; Medical Informatics Bioinformatics; Electronic Medical Records (EMR); Electronic Prescribing Systems (EPS)